Strategi Peningkatan Kemampuan Sistem Navigasi Pesawat C-212-200 dalam Operasi Modifikasi Cuaca (Studi Kasus: KTT G20 Bali 2022) - Sudiawan, Made; Hadi, Yulianto; Asmoro, Novky (MASALIQ, 2025)
This study examines the enhancement of the C-212-200 aircraft’s navigation system capability in supporting Weather Modification Operations (OMC) during the G20 Summit held in Bali in 2022, with a focus on the implementation of the Traffic Collision Avoidance System (TCAS) and Transponder Mode S as part of the system's modernization. The objective of the research is to analyze the effectiveness of integrating these two systems in improving flight safety, situational awareness, and operational efficiency. A descriptive qualitative approach with a case study design was employed, involving technical interviews, field observations, and document analysis within an operational unit of the Indonesian Air Force. The findings indicate that TCAS significantly enhances pilot situational awareness by providing real-time Traffic Advisory (TA) and Resolution Advisory (RA), enabling prompt and accurate conflict avoidance maneuvers. Meanwhile, Transponder Mode S strengthens two-way communication between the aircraft and Air Traffic Control (ATC) through selective interrogation, allowing precise transmission of aircraft position, identification, and altitude data. The integration of both systems has been shown to reduce pilot workload, minimize mid-air collision risk, and improve decision-making effectiveness, especially in high-traffic airspace such as during the G20 Summit. The study also highlights non-technical challenges, particularly the limited readiness of human resources—including avionics technicians and pilots—who require further training in operating and maintaining integrated digital navigation systems. Overall, the modernization of the C-212-200 navigation system through TCAS and Mode S proves effective in supporting non-combat flight operations more safely and efficiently, and represents a strategic step toward civil–military interoperability and digital transformation within the national air defense system.